Antitumor Effect of Si-Jun-Zi Decoction on SGC7901 Gastric Cancer Cells by CMTM2 Activation. (14th July 2022) - Li, Xiangnan; Chen, Wenna; Miao, Lanying; Sun, Hongwei; Gao, Xia; Guo, Shengnan; Zhang, Yueshi; Yang, Yufeng; Guo, Junfu
Abstract : The Si-Jun-Zi decoction (SJZ), a traditional Chinese medicine (TCM) formula, is used clinically against multiple malignancies, including gastric cancer (GC). In previous study, we have shown that SJZ plays an anticancer role in SGC7901 cell xenograft mice models. However, the underlying mechanisms are unclear. The objective of this study was to evaluate the effect and mechanism of SJZ on the proliferation, migration, invasion, and cancer stem cell-like properties of GC cells. High-throughput mRNA sequencing analysis was performed to investigate the global alterations in gene expression in xenograft tumors, and 56 significantly differentially expressed genes (43 upregulated and 13 downregulated genes) were identified between the SJZ group and the Model group totally. We focused on CMTM2, which was significantly increased after SJZ intervention, as a candidate target gene of SJZ. The results indicated that CMTM2 expression was elevated in SJZ-treated SGC7901 cells and knocking-down CMTM2 expression partially hampered the inhibitory effects of SJZ on the proliferation, migration, and invasion of GC cells. Moreover, SJZ treatment repressed the spheroid and colony-forming capacity in GC cells, accompanied by downregulation of stem cell markers including SOX2, NANOG, and CD44. CMTM2 knockdown antagonized the effects of SJZ on the cancer stem cell-like properties of SGC7901 cells. Thus, SJZ effectively suppressed the proliferation, migration, invasion, and cancer stem cell-like properties of GC cells in vitro by upregulating CMTM2 expression.